EVALUATION OF FUNCTIONAL CAPACITY OF EXERCISE OF PATIENTS OF LEPROSY SEQUELS (Fiep Bulletin - online, 2011)
Introduction: The aim of this study was to evaluate the exercise capacity of patients suffering from leprosy before and after an exercise program, attended the Center for Physical Rehabilitation, State University of Paraná (Unioeste), campus of Cascavel. Methods: 19 patients suffering from leprosy were evaluated before and after a physical training program with flexibility exercises (stretching), muscle strengthening, aerobic and relaxation. For the analysis included the incremental shuttle walking test (SWT), maximum oxygen uptake (peak VO2) testing quadriceps muscle strength by testing a repetition maximum (1RM) and grip strength. Results: The test results showed that SWT after treatment increased the distance walked by 13% and maximal oxygen consumption peak VO2 increased 11%. The strength of the quadriceps in both legs also increased by 16%. As for the grip strength has increased by 12%. Conclusions: The proposed training exercise proved to be sufficient to significantly increase functional exercise capacity and quadriceps muscle strength in individuals with leprosy sequels.
Keywords: leprosy; functional capacity; exercise